An investigation of policy incentives for delaying public pension benefit claims. (17th April 2020) - Kitamura, Tomoki; Nakashima, Kunio
Abstract : Purpose: The purpose of this study is to examine the potential and cost of policy incentives for individuals to defer public pension (social security) claims. Design/methodology/approach: Using Internet survey experiments, the impacts of introducing three potential policies to defer public pension claims are examined: (1) a tax incentive for private term pension premiums, (2) a tax incentive for private term pension benefits and (3) a tax disincentive for financial asset holdings. Effectiveness of information provision regarding projection of future financial assets is also examined. Findings: Tax incentives have a certain impact on deferment of public pension claims. Among incentives, increase of benefits is the most effective one. Providing information regarding future financial assets reduces incentives. Originality/value: This study is original in measuring cost for delaying public pension claims according to incentives and information provision.